Adaptation of Convergence by Local Media Pikiran Rakyat and AyoBandung.com - Ridwan Saleh Fadillah; Aceng Abdullah; Abie Besman (Jurnal Kajian Jurnalisme, 2022)
Convergence occurs because of the development of the internet, social media, and digital technology. In the realm of journalism, convergence refers to the practice of producing, distributing, and consuming content for multiple platforms in the form of text, photos, and videos by a single newsroom. The development of technology then gave birth to many disturbances and possibilities. Convergence challenges the media industry's already stable business model to adapt to changes. The purpose of this study is to discuss and compare how the adaptation and application of convergence that the local media "Pikiran Rakyat" and AyoBandung.com have tried to use using convergence theory in Rich Gordon's media organization. This research uses a case study method with a comparative qualitative approach that tries to explain how the application of convergence to "Pikiran Rakyat" and AyoBandung.com and compares how the two media put it into practice. The results showed that; the ownership of "Pikiran Rakyat" and AyoBandung.com adapted convergence by creating media groups and targeting local media as branches or media partners; on tactics, "Pikiran Rakyat" and AyoBandung.com cooperate in news creation with branches or partners and other media, both media focus on programmatic advertising as a source of income; on the structure, "Pikiran Rakyat" and AyoBandung.com implement newsroom 3.0; in gathering information, the journalists of Pikiran Rakyat and AyoBandung.com in carrying out their coverage only required to bring a smartphone; at the presentation, "Pikiran Rakyat" and AyoBandung.com carried out the action of packaging content to various platforms.